PEMANFAATAN SUMBER DAYA HUTAN DI KAWASAN HUTAN KEMASYARAKATAN OI RIDA DESA MARIA UTARA KECAMATAN WAWO KABUPATEN BIMA - Afrizal, Afrizal; Markum, Markum; Setiawan, Budhy (Universitas Pattimura, 2024)
Non-Timber Forest Products (NTFP) are one of the resources that the community in Community Forest can manage. Optimal and efficient use of forest resources will significantly influence improving the standard of living of people who utilize forest resources. However, the community still needs to do it optimally. Forest resources contained in forests have important values that can meet social, environmental, ecological, and economic needs. This study aims to determine the types and utilization of NTFPs in Oi Rida Community Forest, analyze farmers' incomes, and analyze farmer categories based on the World Bank's poverty approach. The research method used to fulfill the research data was a structured interview with 38 HKm respondents. The results showed that there were 18 types of NTFPs with a total plant presence of 10,657 tons/ LLG, including candlenut, coffee, avocado, durian, cloves, bamboo, lamtoro, ginger, turmeric, chili, porang, ginger, vanilla, lemongrass, cassava, keladi, banana, and honey. Total income of Rp. 178,845,583 LLG per year with an average of Rp. 4,706,463 LLG per year. The amount of income from the use of HHBK converted into rupiah, spent to obtain goods or services of US 1.25 or equivalent to Rp 18,332.43 per day, and the average income of Rp 4,706,463 per year to Rp 4,222 per day. This income value is classified as non-prosperous farmers (poor) because the income per person daily does not meet US 1.25 or equivalent to Rp. 18,332.43.